Show No Weakness: Sequentially Consistent Specification of TSO Libraries - Gotsman, Alexey; Musuvathi, Madan; Yang, Hongseok (International Symposium on Distributed Computing (DISC '12), 2012)
Modern programming languages, such as C++ and Java, provide a sequentially consistent (SC) memory model for well-behaved programs that follow a certain synchronization discipline, e.g., for those that are data-race free (DRF). However, performance-critical libraries often violate the discipline by using low-level hardware primitives, which have a weaker semantics. In such scenarios, it is important for these libraries to protect their otherwise well-behaved clients from the weaker memory model. In this paper, we demonstrate that a variant of linearizability can be used to reason formally about the interoperability between a high-level DRF client and a low-level library written for the Total Store Order (TSO) memory model, which is implemented by x86 processors. Namely, we present a notion of linearizability that relates a concrete library implementation running on TSO to an abstract specification running on an SC machine. A client of this library is said to be DRF if its SC executions calling the abstract library specification do not contain data races. We then show how to compile a DRF client to TSO such that it only exhibits SC behaviors, despite calling into a racy library.